Energy Use and Economic Growth Nexus in Central Africa: A Longitudinal Analysis (1990-2023) - Effiong, Mfonobong Okokon; Hosu, Yiseyon Sunday (International Journal of Energy Economics and Policy, 2025)
This research examines the interconnection between energy consumption and economic expansion in Central Africa, utilizing advanced econometric methods to guarantee accurate and dependable outcomes. The findings reveal that energy usage and carbon emissions positively impact economic growth, whereas alternative nuclear energy sources have an adverse effect. In contrast, renewable electricity production and agricultural employment showed no significant impact. Notably, a 1% increase in energy consumption yields a 0.4169% rise in economic growth, and a 1% increase in CO2 emissions results in a 0.0669% growth. Cointegration analysis confirmed a long-term equilibrium relationship among these variables at a 1 % significance level, indicating that all the variables are cointegrated. This study contributes to the ongoing discussion on energy consumption, economic growth, and environmental policies, offering robust evidence of their dynamic interplay. The results align with existing research, providing fresh insights and informing policymakers, researchers, and stakeholders about the intricate relationships between energy use, growth, and environmental sustainability in Central Africa.